2004
DOI: 10.1172/jci200420732
|View full text |Cite
|
Sign up to set email alerts
|

Ornithine decarboxylase is a target for chemoprevention of basal and squamous cell carcinomas in Ptch1+/– mice

Abstract: Solar ultraviolet B (UVB) radiation induces cutaneous ornithine decarboxylase (ODC), the first enzyme in the polyamine-biosynthesis pathway, which drives continued proliferation and clonal expansion of initiated (mutated) cells, leading to tumorigenesis. Therefore ODC is a potentially important target for chemoprevention of basal cell carcinomas (BCCs), the majority of which have mutations in the tumor-suppressor gene known as patched (PTCH). To assess this possibility, we first overexpressed ODC in the skin o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 53 publications
3
48
0
Order By: Relevance
“…Experimental data indicated that tumor development and progression to a malignant phenotype were dependent on the elevated levels of ODC and polyamines (45). Hence, assessment of mucosal ODC activity may be of value as a marker for the potential risk of malignancy in the human large bowel and upper gastrointestinal tract (46), and as a molecular target for the chemoprevention of some carcinomas (47).…”
Section: Discussionmentioning
confidence: 99%
“…Experimental data indicated that tumor development and progression to a malignant phenotype were dependent on the elevated levels of ODC and polyamines (45). Hence, assessment of mucosal ODC activity may be of value as a marker for the potential risk of malignancy in the human large bowel and upper gastrointestinal tract (46), and as a molecular target for the chemoprevention of some carcinomas (47).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials with DFMO have shown no or only limited overall survival benefits in cancer patients, which most probably relates to the cytostatic rather than cytotoxic effect of DFMO in vivo (11). The drug was relatively well tolerated, and more recent studies implicate an interesting role of DFMO as a chemopreventive drug for use in, for example, colorectal cancer, squamous cell carcinomas, and prostate cancer (11,29). The combined effect of DFMO and antiangiogenic strategies has, to our knowledge, never been tested.…”
Section: Introductionmentioning
confidence: 99%
“…These sustained high levels of putrescine lead to alopecia, the development of follicular dermal cysts, increased nail growth, and skin wrinkling. With regard to tumor development, the targeted expression of ODC to the skin also increases the susceptibility of these mice to skin tumor formation following a variety of initiating events including carcinogens (O'Brien et al, 1997;Chen et al, 2000), UV irradiation (Ahmad et al, 2001), and oncogenes (Smith et al, 1998;Tang et al, 2004;Lan et al, 2005). The treatment of newborn or adult K6/ODC transgenic mice with a single topical application of the carcinogen 7, 12-dimethylbenz[a]anthracene (DMBA) yields papilloma formation six to eight weeks later without the use of tumor promoting agents (O'Brien et al, 1997;Peralta Soler et al, 1998).…”
Section: Odc and Nonmelanoma Skin Tumorigenesismentioning
confidence: 99%
“…Bi-transgenic mice expressing both skin-targeted ODC and the v-Ha-ras oncogene develop spontaneous keratoacanthomas and squamous cell carcinomas, whereas no tumors develop in the mono-transgenic mice (Smith et al, 1998;Lan et al, 2005). On the other hand, basal cell carcinomas develop in mice that are both heterozygous null for the patched tumor suppressor gene and overexpressing ODC in follicular cells (Tang et al, 2004).…”
Section: Odc and Nonmelanoma Skin Tumorigenesismentioning
confidence: 99%
See 1 more Smart Citation